What to eat when : a strategic plan to improve your health & life through food - Roizen, Michael F; Crupain, Michael; Spiker, Ted (National Geographic, 2019)
"NY Times best-selling author Dr. Michael Roizen reveals how the food choices you make each day--and when you make them--can affect your health, your energy, your sex life, your waistline, your attitude, and the way you age. What if eating two cups of blueberries a day could prevent cancer? If drinking a kale-infused smoothie could counteract missing an hour's worth of sleep? When is the right time of day to eat that chocolate chip cookie? And would you actually drink that glass of water if it meant skipping the gym? This revolutionary guide reveals how to use food to enhance our personal and professional lives--and increase longevity to boot. What to Eat When is not a diet book. Instead, acclaimed internist Michael Roizen and certified physician Michael Crupain offer readers choices that benefit them the most--whether it's meals to help them look and feel younger or snacks that prevent diseases--based on the science that governs them"--